Difference between post curing composite hardness with heating using dry sterilizer and radiation using light box - Widyasari, Ratih; Fadil, Mochammad Richata; Sukartini, Endang (Padjadjaran Journal of Dentistry, 2010)
Introduction: Composite resin has been used as a restoration material for quite a long time. Two different methods were expected to show result of which method that would be the most promising. Aim of study is to analyzed differences the hardness of one composite resin subjected to two post curing treatments. Methods: This study was a true experimental research (in vitro). The subjects were 30 specimens of the hybrid light cured resin composites made in a mold (6 mm diameter and 4 mm high). The hardness of all specimens were tested using Rebound Hardness Tester. Data were compared using ANOVA and post hoc analysis (for pairwise independent groups) using t-tests. Results: This study showed that post curing treatment by heat (for 10 min at 110 oC ) showed higher hardness (p<0.005). Conclusion: There was difference of hardness between two methods of post curing. Moreover, post curing with dry heat sterilizer at 110oC for 10 min was found to be the most promising post curing method.